2019
DOI: 10.3389/fpsyt.2019.00489
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Study Investment in Italian College Students. An Analysis of Loscalzo and Giannini’s (2017) Studyholism Comprehensive Model

Abstract: Loscalzo and Giannini (2017) recently proposed the construct of studyholism (or obsession toward study) and a theoretical model highlighting its potential antecedents and outcomes. This study aims to analyze some of these antecedents and outcomes by means of a path analysis including both studyholism and study engagement. The participants are 1,958 Italian college students aged between 18 and 60 years ( M age = 23.53 ± 4.43) and heterogeneous as far as their year and major of study are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
45
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(161 citation statements)
references
References 102 publications
(141 reference statements)
19
45
0
16
Order By: Relevance
“…Future studies should use causal models to test the causal relationships between the antecedents and outcomes of studyholism and study engagement proposed by Loscalzo and Giannini (2017a) . One first attempt in this direction has recently been made by Loscalzo and Giannini (2019a) through their path analysis model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should use causal models to test the causal relationships between the antecedents and outcomes of studyholism and study engagement proposed by Loscalzo and Giannini (2017a) . One first attempt in this direction has recently been made by Loscalzo and Giannini (2019a) through their path analysis model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Loscalzo and Giannini (2017a) developed a comprehensive model of studyholism that comprehends its antecedents and outcomes, and that they recently tested in many of its suggested variables ( Loscalzo & Giannini, 2019a ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, since Loscalzo and Giannini believed that unveiling the real nature of a new potential clinical condition requires avoiding a confirmatory approach [refer to Kardefelt-Winther (2015) concerning the need to avoid an a priori assumption of addiction when analyzing new potential behavioral addictions], they reviewed some elements of their preliminary definition ( Loscalzo and Giannini, 2017b ) based on their empirical findings. In fact, the results of the outcomes associated with Engaged and Disengaged Studyholism showed that students demonstrating Disengaged Studyholism are not the most impaired type of students in all the functional areas ( Loscalzo and Giannini, 2019a ; Loscalzo, 2021 ). Hence, Loscalzo and Giannini (2019a) suggested conceptualizing both Disengaged and Engaged Studyholics as clinical types of Studyholism and using the following two specifiers: (i) Level of study engagement (high, average, or low); (ii) Area of functional impairment (academic, social, or both).…”
Section: Introductionmentioning
confidence: 98%
“…After the first publication by Loscalzo and Giannini (2017b) , the definition of problematic overstudying as a condition more similar to an obsession—or Studyholism (e.g., Loscalzo and Giannini, 2017b , 2018a , 2018b )—than to addiction (i.e., Study Addiction; Atroszko et al, 2015 ), or as an OCD-related disorder, has been substantiated by a thorough comparison of DSM-5 ( American Psychiatric Association [APA], 2013 ) diagnostic criteria for OCD, substance-use disorder, and obsessive-compulsive personality disorder ( Loscalzo and Giannini, 2018a ). Moreover, worry, an internalizing feature contributing to OCD ( Comer et al, 2004 ), proved to be a strong predictor of Studyholism both in college ( Loscalzo and Giannini, 2019a ) and adolescent ( Loscalzo, 2021 ) students. Though, the authors concluded these papers by underlining that the literature concerning problematic overstudying is too scant to reach any firm conclusion and that more studies are needed to uncover its real internalizing and/or externalizing nature.…”
Section: Introductionmentioning
confidence: 99%